PERILAKU HARGA DAN PEMASARAN IKAN HASIL TANGKAPAN DI PROPINSI BENGKULU - Sukiyono, Ketut; Kaban, Harisma Ika (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
The aims of this research are to analyze the market price of fish commodity and to forecast behaviour of fish price. Fish types that are analysed in this research are tongkol. The data consist of weekly data of tongkol in the four main market in Bengkulu for the period of 2002 to 2004 are used. The analysis of weekly prices used table analysis and linear regression model involving seasonal fishing dummies. Long run dynamic price equilibrium is analysed using linear regression model based on Cobweb model are estimated using OLS method while autocorrelation problems is overcome by Cochrane-Orcutt. From the trend analysis price tongkol fish result, it is concluded that the slope in Argamakmur and Curup was positive. Meanwhile, for tenggiri fish there was Bengkulu, Manna and Argamakmur that having a positive slope. Based on price behaviour estimation, it can be concluded that lagged price of tongkol is a signifikan factor in determining the fish price in all markets respectively. Moreover, marketing system analysed result that the price in Bengkulu market as a producer market has a signifikan influance to the price of fish in consumen market.